Fabrication luminescence and radiation shielding properties of Gd2O3–La2O3–ZnO–B2O3–Sm2O3 glasses - Kaewjaeng, S.; Kothan, S.; Wantana, N.; Kim, H. J.; Rajaramakrishna, R.; Jumpee, C.; Limsuwan, P.; Kaewkhao, J. (My University, 2023)
The purpose of developing high transparency radiation shielding materials and luminescence materials with stoichiometric ratio of xGd2O3:10La2O3:10ZnO:(79-x) B2O3: 1Sm2O3 where x = 0, 5, 10, 15, and 20 mol% using melt quenching technique. The physio-optical properties such as molar volume, density, concentration of rare-earth ions, polaron radius, inter-ionic radius, optical basicity, average distance between rare-earth ions, and optical packing density of the present glasses has been evaluated. The glass samples obtained show high density which is vital factor for radiation shielding. The absorption spectra show significant of bands Sm3+ ions. The FTIR results of Gd-La-Zn-B-Sm (Gd-1Sm) glass samples show signature borate BO3 and BO4 vibrational units in Gd-1Sm glass samples. The μ, μm, HVL, TVL, and MFP were evaluated and showed that the values decrease with increasing X-ray energy whereas increase with an increase in Gd2O3 content suggesting their potential use in X-ray diagnosis regions. The HVL value was compared with commercial windows, concrete, Serpentine and X-ray windows and found that the glasses doped with 10 mol%, 15mol%, and 20 mol% Gd2O3 content showed better results than X-Ray windows at 10 kVp. The emission and excitation spectra of glass samples were studied and emission spectra show orange emission bands. The experimental lifetime analysis shows that the glass samples show decreasing trend from 1.161 to 1.128 ms with an increase in Gd3+ ions exhibiting single exponential nature.
Keywords: Glass; Luminescence; Radiation; Shielding; X-ray